Financial Performance Analysis of PT. Indosat, Tbk Before and After the Merger - Matruty, Dinatonia Jovery (Jurnal Ekonomi, 2024)
PT. Indosat is a company that merged with PT. Hutchison 3 Indonesia in 2022. To compare the company's financial performance before and after the merger, this writing was carried out by utilizing financial reports for each of the 2 years before the merger (2020-2021) and after the merger (2022-2023), then the data was processed using the DuPont System method and analyzed. The results of the Dupont system analysis show that PT. Indosat has the ability to generate profits for owners from its own capital very well before the merger, especially during the transition period because ROE (0.05) in 2020 becomes 0.67 in 2021 before the merger, and tends to decrease from 0.17 in 2022 to 0.14 in 2023 after the merger. PT Indosat's financial performance before the merger was poor and increased to very good from 2020 to 2021, and after the merger the financial performance decreased quite a lot, but was still classified as good